2017
DOI: 10.3747/co.24.3133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Alcoholic Liver Disease on Recurrence Rate and Liver Regeneration after Liver Resection for Colorectal Liver Metastases

Abstract: Background Resection of metastases is the only potential cure for patients with liver metastasis from colorectal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…However, several studies in humans suggest that fatty liver and liver fibrosis may enhance liver metastasis. 8,9,[182][183][184][185][186][187][188] A large prospective cohort study of 2,715 patients who underwent resection for colorectal cancer liver metastases demonstrated that liver metastasis recurrence was higher in steatotic livers. 8 Another study of 953 patients with liver metastases after curative resection of colorectal cancer showed a fourfold increase in the risk of liver metastasis in fibrotic livers.…”
Section: Inflammation Mediates the Establishment And Growth Of Liver mentioning
confidence: 99%
“…However, several studies in humans suggest that fatty liver and liver fibrosis may enhance liver metastasis. 8,9,[182][183][184][185][186][187][188] A large prospective cohort study of 2,715 patients who underwent resection for colorectal cancer liver metastases demonstrated that liver metastasis recurrence was higher in steatotic livers. 8 Another study of 953 patients with liver metastases after curative resection of colorectal cancer showed a fourfold increase in the risk of liver metastasis in fibrotic livers.…”
Section: Inflammation Mediates the Establishment And Growth Of Liver mentioning
confidence: 99%
“…Previous animal studies have demonstrated that high‐fat diet (HFD)‐induced NAFLD promotes the tumor growth of CRC and PDAC liver metastasis . Large prospective and retrospective human cohorts have demonstrated that cancer patients with NAFLD have increased risk of liver metastasis and for recurrence after resection of liver metastasis compared with patients without NAFLD . The increased prevalence of obesity and NAFLD will likely increase the occurrence of liver metastasis.…”
mentioning
confidence: 99%
“…However, liver macrophages as well as tumor‐associated macrophages (TAMs) could promote a pro‐metastatic niche formation in the liver, likely by polarizing to M2 macrophage, to enhance the growth of metastatic tumor cells that survived the initial tumoricidal attack. Inflammatory, fibrotic, and fatty liver microenvironment enhances liver tumor growth . Indeed, in a NAFLD condition, CD4 + T cells are depleted and tumor surveillance is impaired, which promotes hepatocellular carcinoma (HCC) growth .…”
mentioning
confidence: 99%
“…After hepatectomy, the incidences of mortality and morbidity are dependent on the volume and function of the residual liver[ 17 - 20 ]. Previous reports have demonstrated that steatosis impaired liver regeneration and caused liver dysfunction after hepatectomy[ 11 , 12 ]. NASH has been proposed to cause liver failure rather than steatosis because NASH presents with not only steatosis but also fibrosis, inflammation, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Steatosis is a risk factor for postoperative liver failure[ 11 , 12 ]. A number of clinical studies revealed that steatosis caused severe mortality and morbidity after liver resection compared with normal liver following liver resection[ 11 , 12 ]. In experimental models, hepatectomy of fatty livers resulted in suppressed liver regeneration and survival rates[ 13 - 16 ].…”
Section: Introductionmentioning
confidence: 99%